Ethyl methanesulfonate-induced mutagenesis generates genetic and morphological variations in an elite Argentine sugarcane genotype - Di Pauli, Valentina; Fontana, Paola Daniela; Lewi, Dalia Marcela; Felipe, Arturo; Erazzu, Luis Ernesto (Springer Nature, 2025)
The complexity of the sugarcane genome, the narrow genetic base of subtropical germplasm, and the extended breeding and selection cycle pose significant challenges to conventional breeding methods. In vitro mutagenesis offers an alternative approach to generating genetic variability by harnessing both somaclonal variation and induced mutations. An in vitro mutagenesis protocol, using the chemical mutagen ethyl methanesulfonate (EMS) in an elite Argentine sugarcane cultivar, was developed. The resulting genetic variability was assessed in the field in plant and first ratoon crops. Six-week-old embryogenic calli were treated with 8, 16, 32, and 48 mM EMS. Plants were regenerated from treated calli and acclimatized in a greenhouse. The lethal dose LD50 for regeneration capacity was 31.68 mM EMS, whereas LD25 was 17.71 mM EMS. Based on these results, the plants from the 16 and 32 mM EMS treatments were phenotypically assessed in the field. These assessments showed that EMS treatments exhibited phenotypic variability due to genetic changes. Traits such as the number of stalks, stalk length, stalk weight, internode length, and Brix showed an increase in the population mean in the EMS treatments compared with the wild type. Some traits maintained changes from one year to the next, whereas others reverted to the wild-type genotype values in the second year. Mutagenic treatments generated greater and more stable genetic variation than somaclonal variation, supporting their use as effective tools for sugarcane improvement. Based on agronomic traits, 23 mutant plants were selected and advanced to subsequent generations.